2014
DOI: 10.1073/pnas.1400683111
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 interrupts ATR-Chk1 signaling to allow oncovirus-mediated cell proliferation

Abstract: DNA damage response (DDR) is a signaling network that senses DNA damage and activates response pathways to coordinate cellcycle progression and DNA repair. Thus, DDR is critical for maintenance of genome stability, and presents a powerful defense against tumorigenesis. Therefore, to drive cell-proliferation and transformation, viral and cellular oncogenes need to circumvent DDRinduced cell-cycle checkpoints. Unlike in hereditary cancers, mechanisms that attenuate DDR and disrupt cell-cycle checkpoints in spora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 43 publications
2
78
0
Order By: Relevance
“…For the flow cytometry experiment depicted in Fig. 5B, combinations of siRNA (targeted or scrambled) and FITC-scrambled siRNA were transfected at a 3:1 ratio to identify transfected cells (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the flow cytometry experiment depicted in Fig. 5B, combinations of siRNA (targeted or scrambled) and FITC-scrambled siRNA were transfected at a 3:1 ratio to identify transfected cells (12).…”
Section: Methodsmentioning
confidence: 99%
“…Staining and microscopy were performed as described previously (9,12). Briefly, cells were stained as described above for flow cytometry by using rabbit anti-human STAT3 (Santa Cruz Biotechnology) followed by FITC-anti-rabbit IgG (Life Technologies), washed, cytospun onto glass slides, air dried, and mounted with 4=,6-diamidino-2-phenylindole (DAPI) Prolong Gold Antifade (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Since chemical inhibitors are often associated with off-target effects, we used previously validated siRNAs (22,30) to specifically inhibit STAT3. Figure 3A shows that, compared to scrambled-siRNA-treated cells, introduction of 2 different siRNAs targeting STAT3 into latently infected cells resulted in significant increases in mRNA levels from ORF50, ORF59, ORF9, and ORFK8.1.…”
Section: High Levels Of Stat3 Mark Kshvmentioning
confidence: 99%
“…Activation of STAT3 plays important roles not only in cell proliferation, apoptosis, as well as tumor angiogenesis, invasion, and migration, but also in virus infection [3,4,7,8]. Mammalian viruses, including DNA and RNA virus, could activate STAT3 for efficient infection [3,49].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian viruses, including DNA and RNA virus, could activate STAT3 for efficient infection [3,49]. Our previous studies demonstrated that fish STAT3 was involved in Singapore grouper iridovirus (SGIV) infection, and inhibition of STAT3 activation decreased virus replication and inhibited virus induced paraptosis [10].…”
Section: Discussionmentioning
confidence: 99%